Mitochondrial genome of Lonicera macranthoides: features, RNA editing, and insights into male sterility - Chen, Zhong; Zhuo, Wei; Wang, Yuqi; Qi, Junpeng; Liu, Li; Lu, Sheng’E.; Wang, Han; Sun, Tao; Wang, Liqiang; Ren, Fengming (Frontiers in Plant Science, 2025)
IntroductionMitochondria are essential organelles that provide energy for plants. They are semi-autonomous, maternally inherited, and closely linked to cytoplasmic male sterility (CMS) in plants. Lonicera macranthoides, a widely used medicinal plant from the Caprifoliaceae family, is rich in chlorogenic acid (CGA) and its analogues, which are known for their antiviral and anticancer properties. However, studies on the mitogenome of L. macranthoides still remain limited.MethodsThe mitochondrial DNA contained in the whole genome DNA was extracted from a male sterile cultivar of L. macranthoides, named ‘Yulei 1’. Next-generation sequencing (NGS) and third-generation sequencing (TGS) technologies were combined to obtain the mitogenome. RNA editing events were identified by integrating the mitogenome data with RNA sequencing data from leaf, stem, and flower tissues. The potential causes of male sterility in ‘Yulei 1’ were analyzed based on the loss of functional genes, mitogenome rearrangements, RNA editing events, and open reading frames (ORFs).Results and discussionThe complete mitogenome of L. macranthoides ‘Yulei 1’ was obtained for the first time, with a length of 1,002,202 bp. It contains 48 protein-coding genes (PCGs), 26 tRNA genes, and 3 rRNA genes. Additionally, 79 simple sequence repeats (SSRs), 39 tandem repeats, and 99 dispersed repeats were identified. Among these, two direct repeats (RP1a/1b, RP2a/2b) and two inverse repeats (RP3a/b, RP4a/b) may facilitate mitogenome recombination. Gene transfer analysis revealed that 4.36% and 21.98% of mitogenomic sequences mapped to the chloroplast and nuclear genomes, respectively. Phylogenetic analysis indicated that L. macranthoides is closest to L. japonica at the mitogenome level. Notably, RNA editing events varied across different plant tissues, with 357 editing sites in 30 PCGs in leaves, 138 sites in 24 PCGs in flowers, and 68 sites in 13 PCGs in stems. Finally, all indications of CMS in the mitogenome were screened, including the detection of ORFs, and the findings showed no mutations in the mitogenome that would explain the sterility of ‘Yulei 1’. Overall, our study provides a complete mitogenome of L. macranthoides, which will aid in its genetic marker exploration, evolutionary relationship analysis, and breeding programs.